PENGARUH BRANDING TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA UNIVERSITAS NEGERI MEDAN: STUDI KASUS PADA UMKM USAHA POP ICE PAK FAREL, - Panjaitan, Ariel Immanuel; Lubis, Adelina; Teviana, T. (Relawan Jurnal Indonesia, 2025)
In the era of globalization, branding is an important factor in determining consumer purchasing decisions, especially for MSMEs such as Pop Ice Pak Farel. This study aims to analyze the effect of branding on purchasing decisions of students at Medan State University and other factors that influence customer loyalty. The method used is a quantitative approach with a survey technique on 31 respondents who have purchased products in the last six months. Data analysis was carried out using simple linear regression. The results of the study indicate that branding, especially product taste and variety, plays a major role in shaping purchasing decisions, followed by packaging design and brand logo. However, price and promotion factors do not significantly affect purchase frequency. These findings indicate that loyalty-based marketing strategies, product innovation, and strengthening visual identity can be effective steps in increasing the competitiveness of MSMEs. In addition, a more structured payment system is needed to overcome transaction constraints. By implementing a more effective strategy, MSME Pop Ice Pak Farel is expected to be able to retain customers and increase consumer loyalty in the long term.